E-Commerce Shopee Indonesia : Empirical Lessons From The Impact Of Digital Marketing, Brand Loyalty On Brand Equity - Istianingsih, Nanik; Susriyanti, Susriyanti; Ariyanto, Ariyanto; Pranawukir, Iswahyu (International Journal of Artificial Intelligence Research, 2024)
The study aims to provide empirical evidence of the impact of digital marketing, brand loyalty on the brand equity of E-commerce Shopee Indonesia. The research method is a survey study through a quantitative approach, assessment based on numbers using statistical calculations, using simple random sampling techniques and data collection techniques in this study using library research, field research, observation, and questionnaires. The research sample was 100 consumers. Data was processed using SPSS version 26. The results of the study indicate that digital marketing, brand loyalty partially and simultaneously have a positive and significant effect on the brand equity of E-commerce Shopee Indonesia. Based on the coefficient of determination (adjust R Square), the independent variables consisting of digital marketing, brand loyalty can contribute to the influence on brand equity